P1127Occurrence, management and outcomes of iatrogenic aortic dissections as a complication of catheter ablation. A multicenter study. (18th June 2020) - Futyma, P R; Aksu, T; Cooper, J M; Schaller, R; Winterfield, J; Payne, J; Omarov, M; Vazquez, O; Guler, T E; Bozyel, S; Zahwe, F; Gautam, S; et al.
Abstract: Background: Data on occurrence, management and outcomes of iatrogenic aortic dissections (IAD) as a complication of catheter ablation (CA) do not exist. Purpose: To evaluate multicenter data on occurrence, management and outcomes of IAD as a complication of CA. Methods: Data on occurrence, management and outcomes of documented vascular dissections from 10 centers were evaluated. Results: IADs occurred in 7 patients (2 females, age 63 ± 8 years). Indications for CA were frequent premature ventricular complexes (PVC)/ventricular tachycardia (VT) in 6 patients (86%) and left-sided accessory pathway in the remaining one (14%). Hypertension was most frequent comorbidity (4 pts, 57%). All IADs occurred during retrograde advancement of ablation catheter. In the vast majority of patients creation of IAD during catheter advancement was not associated with any symptoms (6 pts, 86%). IAD was initially detected using trans-luminal angiogram in 5 (71%) and further confirmed using computed tomography (CT) (5 pts, 71%), conventional angiography (2 pts, 28%) and ultrasound (2 pts, 28%). One IAD was detected during CT scan performed for other indication after CA. There was one IAD-related death and IAD was evaluated post-mortem. Follow-up lasted 10 ± 19 months. Four patients were treated conservatively, one patient underwent descending aorta stenting and one femoral artery stenting. Conclusions: IAD during CA is a rare but can be devastating. Early recognition can be difficult. Conservative management of IAD is an option of treatment.